Factors affecting the adoption of online banking service : A case study in Kuching, Sarawak - Michelle Jenai, Anak Nelson Mujah (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This study aims to identify the factors that encourage consumers in Kuching, Sarawak to adopt online banking services. It is a study to identify important elements affecting customers' intention to adopt online banking. An extended Technology Acceptance Model (TAM) namely perceived ease of use and perceived usefulness, perceived trust and security, government support used to identify the relationship towards the intention to use online banking. Four hypothetical situations were proposed in this stud~ Meanwhile, the dependent variable is the elements of the adoption of online banking (customers' intention to use online banking). There were 250 respondents involved in this study which were randomly selected in Kuching, which were conducted via emails and based on personally administered questionnaires from various backgrounds of people. Participation of respondents was purely voluntary. The instrument used for this study was a survey questionnaire. The questionnaire was reliable at alpha coefficient value for each variables was 'r '=+0.50. Descriptive statistic that was used to analyze the demographic data in this study is the frequency (n) and percentage (%). Meanwhile, the inferential statistic used in this study was Pearson Coefficient Correlation 'r'. The overall findings show that all of the factors that had been analyzed above were positively affecting the customers' intention to adopt online banking services. Perceived usefulness and perceived trust and security were strongly correlated with the adoption of online banking. Meanwhile, perceived ease of use and government support was moderately influencing the customers' intention to adopt online banking. The result of this finding might be useful for the practitioners especially the banks that provide online services. This might provide banking industry some insights into factors that will likely effect consumers acceptance of online banking technology and the highlights areas of consideration in the adoption of these new technologies. Relative advantage and compatibility jump to the top of the list ofcharacteristics of online banking technology to highlight for consumers .